Occurrence, genotyping, and health risk of Cryptosporidium and Giardia in recreational lakes in Tianjin, China. (15th September 2018) - Xiao, Shumin; Yin, Pengna; Zhang, Yan; Zhao, Xiaoyun; Sun, Liping; Yuan, Hongying; Lu, Jingfang; Hu, Sike
Abstract: Cryptosporidium and Giardia are critical parasites in the etiology of diarrhea worldwide, and often cause waterborne outbreaks. The presence of Cryptosporidium and Giardia in recreational lakes was investigated with molecular characterization, and a comprehensive quantitative microbial risk assessment (QMRA) of protozoan infections was performed, considering multiple exposure pathways, differences in age, sex, and disease severity, and the genotypes of the protozoa. Forty-three (82.7%) and 51 (98.1%) water samples were positive for Cryptosporidium oocysts and Giardia cysts, respectively, with average counts of 3.65 oocysts/10 L and 12.58 cysts/10 L, respectively. Six Cryptosporidium species and three Giardia lamblia assemblages were confirmed with molecular analyses. The protozoan concentration was significantly associated with water turbidity, but not with the total coliform numbers. Swimming in the lakes entailed the highest incidence risk of 5.72 × 10 −4 per person per year (pppy) (95% confidence interval (CI): 0.03–43.33 × 10 −4 ) for Cryptosporidium and 4.04 × 10 −4 pppy (95% CI: 0.01–32.66 × 10 −4 ) for Giardia, whereas wading entailed the lowest risk (2.20 × 10 −4 and 1.70 × 10 −4 pppy, respectively). The annual burdens attributable to recreational-water-associated cryptosporidiosis and giardiasis were 3.44 (95% CI: 0.04–23.51) and 1.81 (95% CI: 0.01–12.96) disability-adjusted life years per 1, 000, 000 individuals per year, respectively. Children were more likely to have an individual disease burden than adults, and males were more likely than females. Sensitivity analysis highlighted the great importance of controlling the proportion of exposed individuals and reducing the frequency of exposure. The methodology and results of this study will allow us to better evaluate and reduce the burden of Cryptosporidium and/or Giardia infections associated with recreational water use in China and other countries. Graphical abstract: Image 1 Highlights: Protozoan incidence, genotypes and risks were studied simultaneously. All detected protozoa except, C. fragile, are potentially infectious to humans. Genotypes, age, sex, and disease severity were considered in the QMRA. Protozoan disease burden violated the WHO threshold of 10 −6 DALYs pppy. Fraction of the population exposed and exposure frequency most affected the risk.